2018
DOI: 10.1002/asi.24109
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Influences of Government Funding and International Collaboration on Citation Impact

Abstract: A recent publication in Nature reports that public R&D funding is only weakly correlated with the citation impact of a nation's articles as measured by the field‐weighted citation index (FWCI; defined by Scopus). On the basis of the supplementary data, we up‐scaled the design using Web of Science data for the decade 2003–2013 and OECD funding data for the corresponding decade assuming a 2‐year delay (2001‐2011). Using negative binomial regression analysis, we found very small coefficients, but the effects of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 16 publications
3
32
0
3
Order By: Relevance
“…R&D investments are also strongly related to citation gains [30, 40, 86–87]. As shown in Fig 3, those countries that invest more than 2% of their GDP into R&D realize higher citation gains than those with lower levels of research investment, although the difference between papers in international collaboration and other papers is smaller.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…R&D investments are also strongly related to citation gains [30, 40, 86–87]. As shown in Fig 3, those countries that invest more than 2% of their GDP into R&D realize higher citation gains than those with lower levels of research investment, although the difference between papers in international collaboration and other papers is smaller.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially the case when grouped according to level of funding intensity, where there may exist important national disparities—particularly in the case of those countries with less than 0.5%. The use of this indicator instead of Government Budget Allocations or Outlays on R&D (GBARD) used in other studies [30, 87] is justified because we are interested in the level of infrastructure, human capital, and commitment in R&D activities for each country. Limiting the analysis only to government spending and/or Higher Education may be justified when analysis is focused in some specific nations [100], but that may exclude outputs and human capital funded by private companies.…”
Section: Discussionmentioning
confidence: 99%
“…Another facet has been the comparison between one-country collaborations and many-country collaborations (Frenken et al, 2005(Frenken et al, , 2010Persson et al, 2004). Bornmann 2017, Leydesdorff et al (2019) and Thelwall and Maflahi (2019) reported significant positive relationship between citations and many-country authorships. These results are similar across models such as OLS, negative binomial and zero-inflated Poisson, with citations measured as counts in WOS or normalised citations.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Comparing scientific impact among countries is fundamental for the development of effective strategies for science financing and assessment ( Vinkler, 1986 ; King, 2004 ; Hermes-Lima et al, 2007a ; Wagner et al, 2018 ). Such comparisons allow the definition of funding strategies based on inputs and outputs of the Research and Development (R&D) system and the identification of countries and institutions with the best performance ( Freeman, 1977 ; Leydesdorff et al, 2019 ). These top performer countries, in turn, can be emulated by less-developed nations.…”
Section: Introductionmentioning
confidence: 99%
“…These metrics are frequently combined in a single indicator, such as the Citations Per Publication (CPP) ( Lehmann et al, 2003 ; Moed, 2005 ; Waltman and van Eck, 2009 ; Vinkler, 2010 ) or the well-known h-index ( Hirsch, 2005 ; Egghe, 2006 ; Glänzel, 2006 ; Hermes-Lima et al, 2007b ; Franceschini and Maisano, 2010 ). However, each index has its caveats, and identifying simple, meaningful metrics for scientific productivity evaluation at country level has been a challenge ( King, 2004 ; Leydesdorff et al, 2019 ). The limitations of the h-index have been vastly discussed in the literature ( Bornmann and Daniel, 2005 ; Waltman and van Eck, 2012 ); and inter-country comparisons using the CPP have problems related to the time frame of an analysis.…”
Section: Introductionmentioning
confidence: 99%